The Power of Objects in Eighteenth-Century British America - Van Horn, Jennifer (Book collections on Project MUSE., 2017)
"Over the course of the eighteenth century, Anglo-Americans purchased an unprecedented number and array of goods. [Van Horn] investigates these diverse artifacts--from portraits and city views to gravestones, dressing furniture, and prosthetic devices--to explore how elite American consumers assembled objects to form a new civil society on the margins of the British Empire. In this interdisciplinary transatlantic study, artifacts emerge as key players in the formation of Anglo-American communities and eventually of American citizenship"--